Fabrication of biopolymer wound dressing by solvent casting technique: article - Anuar Othman, Muhammad; Mustapa, Ana Najwa (2019)
Biopolymers and their applications have been widely studied in recent years. Current wound dressings have disadvantages such as less flexibility, poor mechanical strength, lack of porosity, and a tendency for dressings to adhere onto the wound surface. In this work, two biomaterials i.e. alginate and soy protein isolate (SPI) were used to fabricate biopolymer wound dressing. The aim of this study is to investigate the effect of alginate and soy protein ratio on the chemical and physical properties of the hybrid biopolymer wound dressing and to determine effect of addition glycerol into the fabricated alginate/soy protein wound dressing. The biopolymers were characterized by its physical and chemical analysis such as chemical composition, porosity, surface morphology, thermal degradation using FTIR, SEM, and DSC and TGA, respectively. The alginate weight ratio was ranging between 1, 2% and 3 wt% and 0.5, 1.0 and 1.5 wt% of soy protein ratio, respectively. The synthesized biopolymers were dried by supercritical drying using CO2 at 120 ± 5 bar and 40 oC to remove excess solvent from the hybrid biopolymer wound dressing. Results demonstrated that increase in the alginate content increased the roughness of the biopolymer films whereas the SPI content promotes smother surface onto the film. The addition of glycerol had increased the mechanical strength of the biopolymer film. This study suggests that the characteristics of the biopolymer can be improved by addition of another type plasticizer and different biomaterials to improve the surface morphology of the biofilms as well as thermal stability